Study of Production and Technical Efficiency of Smallholders Oil Palm Plantations in Hatonduhan District, Simalungun Regency, North Sumatera Province - Simatupang, Jones T.; Siregar, M. Akbar; Sibuea, Mhd. Buhari (ITScience (Information Technology and Science), 2025)
Modern management of smallholder oil palm plantations is very much needed to enable smallholder oil palm plantations to follow the progress of management of large oil palm plantations, both state-owned and privately owned. This study aims to determine how production factors influence production and to determine the technical efficiency of smallholder oil palm plantations. The location of the study was determined purposively based on the consideration of the existence of smallholder oil palm plantations in the area. The sample was determined by quota sampling of 150 samples from two villages, namely Buntu Bayu Village and Buntu Turunan Village, each with 75 samples. The analysis involves applying the Multiple Non-Linear Regression Test (Rank Test) alongside Data Envelopment Analysis, focusing on managing smallholder oil palm plantations throughout 2023. The study results show that, partially, the production of smallholder oil palm plantations is significantly positively influenced by each production factor. Conversely, the output of smallholder oil palm plantations is notably affected by various production factors, including land, labor, fertilizer, and pesticides. Most (78.00%) smallholder oil palm plantations are technically inefficient, with an average technical efficiency value of 0.9755. To achieve a technically efficient production process, smallholder plantation farmers must reduce inputs, namely 2.5416% of the land, 4.0501% of labor, 5.5449% of fertilizer, and 3.1165% of pesticides.